1989
DOI: 10.1007/bf00175588
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric deposition of phosphorus and nitrogen in Central Alberta with emphasis on Narrow Lake

Abstract: Average rates of atmospheric deposition of total phosphorus (TP) and total nitrogen (TN) to Narrow Lake, located on sedimentary bedrock in the boreal forest of central Alberta, were 20 and 424 mg m z yr-l, respectively, between 1983-1986. There were no significant differences (P > 0.05) in deposition rates between sites on Narrow Lake, on the lake shore, and on land 18 km away. Deposition of TP, but not TN, followed a distinct pattern during the open-water season; TP was highest just after ice-off (May) and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
51
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 14 publications
15
51
1
Order By: Relevance
“…These seasonal trends agree with many other studies which found that deposition increased in early summer and decreased over the remainder of the summer [32][33][34]. In a review of studies on TP deposition from long-range transport, deposition rates showed a wide range.…”
Section: Total Depositionsupporting
confidence: 90%
See 1 more Smart Citation
“…These seasonal trends agree with many other studies which found that deposition increased in early summer and decreased over the remainder of the summer [32][33][34]. In a review of studies on TP deposition from long-range transport, deposition rates showed a wide range.…”
Section: Total Depositionsupporting
confidence: 90%
“…NADP-reported rates ranged from 2.14 to 8.42 mg m −2 year −1 [24] while our measured rates ranged from 0.04 to 24.82 mg m −2 year −1 . Our measured values appear to be reasonable when compared to other studies [31,33], again with the higher values used for the upper bound being attributed to local sources.…”
Section: Total Depositionsupporting
confidence: 89%
“…The atmospheric input of N can be especially significant to aquatic ecosystems (Shaw et al 1989;Hu et al 1998;Larsen et al 2001) and humans have approximately doubled the rate of N input into terrestrial cycles (Galloway et al 1995;Vitousek et al 1997). Several reports suggest that P deposition should be included more frequently in atmospheric deposition studies (Gomolka 1975;Cole et al1990;Jassby et al 1994;Ahn and James 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have shown that measured deposition rates decreased as collectors were moved from shore to open water (Gomolka 1975;Cole et al 1990) whereas another showed no significant difference between deposition rates measured onshore and offshore (Shaw et al 1989). Another study has shown that measured rates of phosphorus deposition are lower and less variable when automated samplers are placed 15 m from the ground (Pollman et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation